Primary Stability of Zirconia Dental Implants with Cylindrical and Tapered Designs Across Varying Bone Densities: An In Vitro Evaluation - Diogo Fernandes; Francisco Cavaco; Filipe Freitas; Duarte Marques; João Caramês; André Moreira (Dentistry Journal)
Background: While titanium implants are widely recognized for their clinical success, zirconia implants have emerged as a metal-free alternative. This study aimed to evaluate the influence of zirconia implant macrogeometry and bone density on primary implant stability. Methods: Two types of zirconia implants were tested—the Neodent® Zi Ceramic Implant and the Straumann® PURE Ceramic Implant, that were placed into polyurethane foam blocks mimicking different bone densities (10 PCF, 15 PCF, 20 PCF, 30 PCF, and 40 PCF). Each implant type was inserted and removed multiple times, with primary stability measured using resonance frequency analysis via the Osstell® Beacon device. Statistical tests, including the Shapiro–Wilk test, t-tests, the Mann–Whitney U test, and the Kruskal–Wallis test, were applied, with significance set at 5% (p < 0.05). Results: The tapered Neodent® Zi Ceramic Implant consistently showed higher ISQ values across all foam densities compared to the Straumann® PURE Ceramic Implant (p = 0.035). Additionally, lower-density foams exhibited lower stability scores (p < 0.05). Conclusion: The study concludes that both the macrogeometry of zirconia implants and bone density significantly affect primary implant stability. Specifically, tapered implants demonstrated higher stability than cylindrical designs, suggesting that implant macrogeometry and bone density should be considered for optimal primary stability in clinical settings.